2019
DOI: 10.20961/carakatani.v34i1.25974
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Population and Intensity of Cassava Mealybug (Phenacoccus manihoti) Attack on Flores Island

Abstract: This study was conducted to obtain population data and damage due to the attack of <em>Phenacoccus</em><em> manihoti </em>Cassava mealybug pest on cassava plantations on Flores Island. This research was carried out in Ende Regency, Sikka Regency and Nagekeo Regency, East Nusa Tenggara Province (NTT). The research was conducted in October 2017. Method used in this research was descriptive method with direct observation and sampling. Cassava plants that were observed included plants that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…A study was conducted to observe the effect of the number of mealybugs on the intensity of attacks with direct observation and sampling in three areas (Figure 3): Ende, Sikka, and Nagekeo districts. The results showed that Sikka district had the highest intensity of damage (43.3%), followed by Nagekeo district (22%), and Ende district with the lowest intensity, at 20% [92]. The development of the mealybug population is strongly supported by weather conditions with high temperatures and low humidity [93,94].…”
Section: Mealybugsmentioning
confidence: 97%
“…A study was conducted to observe the effect of the number of mealybugs on the intensity of attacks with direct observation and sampling in three areas (Figure 3): Ende, Sikka, and Nagekeo districts. The results showed that Sikka district had the highest intensity of damage (43.3%), followed by Nagekeo district (22%), and Ende district with the lowest intensity, at 20% [92]. The development of the mealybug population is strongly supported by weather conditions with high temperatures and low humidity [93,94].…”
Section: Mealybugsmentioning
confidence: 97%
“…Hama ini pertama kali terdeteksi di Bogor pada tahun 2010 (Muniappan et al 2011). Hingga akhir tahun 2014, kutu putih P. manihoti telah tersebar luas di Pulau Jawa dan Lampung (Abdulchalek et al 2017) serta sejak tahun 2017 ditemukan di Pulau Flores (Pu'u 2019). Kutu P. manihoti bersifat monofag, hanya menyerang tanaman singkong (Cox & Williams 1981).…”
Section: Pendahuluanunclassified